2022
DOI: 10.1088/1741-4326/ac906f
|View full text |Cite
|
Sign up to set email alerts
|

Global E × B flow pattern formation and saturation

Abstract: The E×B flow staircase-like pattern observed in the first principle gyrokinetic numerical experiments of tokamak fusion plasmas forms due to a nonlinear time delay. Simulations demonstrate a finite time delay between the staircase occurrence in particle transport and that in density profile. This novel finding shows that instability can arise from perturbations in transport and then influence the background turbulence. E×B flow staircase plays roles not only in shearing the transport but also as a nonlinear sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[21] is valid only for the initial exponential growth of the modulational instability. The fluid model (1,2) could possibly be extended to CTEM, where zonal density generation seems to play a crucial role [40,41]. Another point is about the importance of density nonlinear structures.…”
Section: Discussionmentioning
confidence: 99%
“…[21] is valid only for the initial exponential growth of the modulational instability. The fluid model (1,2) could possibly be extended to CTEM, where zonal density generation seems to play a crucial role [40,41]. Another point is about the importance of density nonlinear structures.…”
Section: Discussionmentioning
confidence: 99%
“…With the time delay between variations of a field and its flux, the avalanche flux propagation can be jammed to form a seed perturbation (temperature corrugation) of the transport barrier [36]. Note that recent gyrokinetic simulations found that there exists such a time delay in both temperature [60] and density [61]. The jamming occurs when an avalanche is so fast to overtake a wave that can be carried by the system.…”
Section: The E × B Staircase and Its Avalanche Stopping Capabilitymentioning
confidence: 99%
“…[15][16][17][18]. The other approach is the jams model [19][20][21]. In this alternative picture, the staircase forms due to a time delay between temperature modulations and local heat flux.…”
Section: A Backgroundmentioning
confidence: 99%